Ten Years of Entrepreneurship Education at Chinese Universities: Evolution, Problems, and System Building. Issue 3 (3rd May 2016) - Weiming, Li; Chunyan, Li; Xiaohua, Du
Abstract: Entrepreneurship education has experienced four stages of development in Chinese universities, shifting from entrepreneurship show to entrepreneurship education, from teacher training to student education, from classroom teaching to multimodal teaching, and from imparting knowledge to cultivating skills. Currently, the weak links in entrepreneurship education in Chinese universities are primarily reflected in four areas: unsound curriculum design, a lack of qualified teachers for entrepreneurship education, a monotonous model for entrepreneurship education, and imperfect supporting mechanisms for entrepreneurship education. Constructive ideas for the entrepreneurship education system in Chinese universities are: to build a scientific curriculum-based educational system, establish a perfected entrepreneurial practicum system, build up a system for an outstanding corps of qualified teachers, construct a perfected educational model system, and perfect the evaluation system for entrepreneurship education.